Income distribution and labour movement in China after WTO membership: A CGE analysis - Jiao Wang; David Mayes; Guanghua Wan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Using a CGE model, PRCGEM, with an updated 2002 I/O table, this paper explores how earnings will be affected in each of 40 separate industries across 31 regions (or 8 regional blocks) of China for the period 2002–07. Labour movement between regions within China is considered. It is found that the direct contribution of WTO membership is small to the whole economy in terms of growth and development. Real GDP will rise only 6.48 per cent (5.6 per cent) in the pure WTO short-run (long-run) shock. Full economic structure change besides WTO shock makes regional output better-off, especially the coastal regions where the economies are well established. Regional labour movement increases by 69.2 per cent in the long-run closure of full economic structural change during the transition period. When regional labour movement is considered, it is found that the Gini coefficient is slightly decreased.
Keywords: C68; O18; R12; R23; 330; applied CGE modelling; China; WTO; labour movement; inequality; Arbeitsmobilität; Industrielohn; Regionale Einkommensverteilung; China; WTO-Beitritt